Reconstructing the Concept of Bela Negara: From Excessive Jargon to an Empirical Civic-based Approach - Abdullah A Afifi; Andriyaldi Andriyaldi; Hanief Adrian (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2024)
The term bela negara (BN) has been widely used in Indonesian national discourse, often associated with state-led campaigns, ideological ceremonies, and symbolic narratives. However, its application has increasingly shown symptoms of conceptual excessivism, overused, abstract, and disconnected from everyday civic life. This article aims to reconstruct BN into a measurable and meaningful framework through an empirical, civic-based approach. By adapting behavioral and marketing evaluation models, such as customer satisfaction index (CSI), servqual, and theory of planned behavior, this paper proposes the model partisipasi bela negara (MPBN). The model offers six key dimensions: public awareness, perceived relevance, emotional engagement, civic intention, real action, and loyalty to the national narrative. These dimensions enable both scholars and policymakers to assess the effectiveness of BN initiatives based on citizen experience and engagement. The model serves as a strategic tool for transforming BN concept into a participatory, democratic, and context-sensitive concept, particularly relevant in today’s digital and pluralistic society. Rather than functioning as a rigid ideological imposition, BN should evolve into an inclusive civic identity that empowers public participation and strengthens national cohesion through trust, value, and meaningful contribution.